2011
DOI: 10.1038/modpathol.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MYB expression and MYB-NFIB gene fusions in adenoid cystic carcinoma and other salivary neoplasms

Abstract: Recent studies have shown that the recurrent t(6;9)(q22-23;p23-24) translocation in adenoid cystic carcinoma results in a novel fusion of the MYB proto-oncogene with the transcription factor gene NFIB. To determine the frequency of this finding, we used RT-PCR assays of the MYB and MYB-NFIB fusion transcripts, and immunohistochemistry for the MYB protein, to study adenoid cystic carcinomas and other epithelial tumors of the salivary glands, and head and neck region. MYB-NFIB fusion transcript was detected in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
245
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(277 citation statements)
references
References 25 publications
24
245
2
1
Order By: Relevance
“…One consequence of the rearrangement is the overexpression of a fusion transcript (perhaps related to absence of a 3′ negative regulatory element found in the normal MYB mRNA) as well as a largely intact MYB oncoprotein. This leads to deregulation of expression of the MYB target genes, which, in turn, promotes tumorigenesis 28, 31, 32, 33. Alterations of NFIB may also be of significance because mutations that seem to target this gene have been described in some ACCs 24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One consequence of the rearrangement is the overexpression of a fusion transcript (perhaps related to absence of a 3′ negative regulatory element found in the normal MYB mRNA) as well as a largely intact MYB oncoprotein. This leads to deregulation of expression of the MYB target genes, which, in turn, promotes tumorigenesis 28, 31, 32, 33. Alterations of NFIB may also be of significance because mutations that seem to target this gene have been described in some ACCs 24…”
Section: Introductionmentioning
confidence: 99%
“…For those patients who relapse after surgery, 1 older study indicated that the response rate to salvage radiation may be as high as 94%, but long‐term control was achieved in only 10% of the patients 56. Also, radiation is a standard treatment for palliation of brain and bone metastases 31. Of note, modern radiation techniques, such as intensity‐modulated radiation therapy, proton beam, and neutron beam therapies seem to be at least equally effective against ACC 57, 58, 59…”
Section: Introductionmentioning
confidence: 99%
“…There are a handful of salivary gland tumors that have been demonstrated to have recurring cytogenetic abnormalities including adenoid cystic carcinomas [t(6;9) (MYB-NFIB)] [8][9][10], mucoepidermoid carcinomas [t(11:19) (MECT1-MAML2)] [11,12], pleomorphic adenomas (PLAG1 and HMGA2 rearrangements) [13][14][15][16][17], and hyalinizing clear cell carcinoma [t(12;22) (EWSR1-ATF)] [18,19]. In the majority of these tumors, the morphology is distinctive enough to allow for a diagnosis and molecular confirmation is typically not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is some disagreement in the literature regarding the percent of ACC tumors harboring this molecular alteration, most subsequent studies have shown that the majority of ACC have a disrupted MYB gene and/ or evidence of a MYB-NFIB fusion RNA transcript [32][33][34][35][36]. One of the largest independent cohorts separate from the Stenman group came from a study at Stanford University, where 37 cases of ACC were studied by fluorescence in situ hybridization (FISH) of the MYB and NFIB loci, with 65 % of cases showing abnormalities of these loci [34].…”
Section: Introductionmentioning
confidence: 99%